2011
DOI: 10.1007/s00330-011-2175-6
|View full text |Cite
|
Sign up to set email alerts
|

Does the degree of background enhancement in breast MRI affect the detection and staging of breast cancer?

Abstract: The degree of background enhancement affected the detection and staging of breast cancer using MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 12 publications
(21 reference statements)
3
60
1
Order By: Relevance
“…Qualitative background parenchymal enhancement assessment Among the 39 (28111) studies that assessed BPE qualitatively, 7,8,[10][11][12][13]15,17, 38% (15/39) studies were published in 2015 (January-October 2015) and 62% (24/39) studies were published during 2010-2014. Most of the studies were performed in the USA (17/39 studies), the Korea (10/39 studies) and Japan (6/39 studies).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative background parenchymal enhancement assessment Among the 39 (28111) studies that assessed BPE qualitatively, 7,8,[10][11][12][13]15,17, 38% (15/39) studies were published in 2015 (January-October 2015) and 62% (24/39) studies were published during 2010-2014. Most of the studies were performed in the USA (17/39 studies), the Korea (10/39 studies) and Japan (6/39 studies).…”
Section: Resultsmentioning
confidence: 99%
“…8,10,[12][13][14][15]21,23,26,28,[32][33][34][35][36]38,[40][41][42][43][48][49][50][51][52][53][54]57,59,61 In five studies, 11,17,19,29,44 the authors acknowledged that owing to the retrospective nature of the study, it was not possible to analyze the point of menstrual cycle, although, following institutional protocol, screening breast MRI of patients who were pre-menopausal was performed during the second week of the menstrual cycle. In a total of 14 studies, the authors stated the menstrual period.…”
Section: Quantitative Background Parenchymal Enhancement Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have shown that BPE computed from DCE-MRI examinations was a useful cancer risk prediction and/or a cancer diagnostic factor [22,23], this study is different. We investigated and tested a new feature index that is generated based on the bilateral asymmetry of BPE feature values computed from the left and right breasts of one woman.…”
Section: Resultsmentioning
confidence: 57%
“…The CAD schemes first extract and compute dynamic contrast enhancement features from the characteristic kinetic curves generated from a set of the selected pixels located inside the identified and segmented breast lesions, and then apply different machine learning classifiers to distinguish between the malignant and benign lesions [16][17][18][19][20]; for example, one study reported that using a leave-one-case-out testing method, a CAD scheme using a set of selected DCE-MRI features and a Bayesian artificial neural network yielded an area under a receiver operating characteristic (ROC) curve (AUC=0.78±0.04) when applying to a dataset involving 168 malignant and 45 benign breast lesions [21]. Although the previous studies focused on detection and analysis of characteristic kinetic curves computed from the pixels inside the segmented lesions, a recent study also showed that similar to a widely used image-based risk factor, namely, the mammographic density, the background parenchymal enhancement (BPE) evaluated or computed from the entire breast areas depicting on DCE-MRI images also carried useful or higher discriminatory information associated with cancer risk assessment [22] as well as the performance of cancer detection and staging [23].…”
Section: Introductionmentioning
confidence: 99%